Globalization, Fertility and Marital Behavior in a Lowest-Low Fertility Setting - Osea Giuntella; Lorenzo Rotunno; Luca Stella (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using longitudinal data from the German Socio-Economic Panel, we analyze the effects of exposure to globalization on the fertility and marital behavior in Germany, until recently a lowest-low fertility setting. We find that exposure to greater import competition from Eastern Europe led to worse labor market outcomes and lower fertility rates. In contrast, workers in industries that benefited from increased exports had better employment prospects and higher fertility. These effects are driven by low-educated, married men, and full-time workers and reflect changes in the likelihood of having any child (extensive margin). While there is evidence of some fertility postponement, we find significant effects on completed fertility. There is instead little evidence of any significant impact on marital behavior.
Keywords: F14; F16; J13; 330; globalization; labor market outcomes; fertility; marriage